Respuesta :
The quadratic formula is expressed as:
x = (-b +/- √(b^2 - 4ac) ) / 2a
where a, b and c are the coefficients of the quadratic equation with the form ax^2 + bx + c=0
Therefore, the quadratic equation would be:
a = 3
b = -6
c = 8
x = (-(-6) +/- √((-6)^2 - 4(3)(8) ) / 2(3)
Hope this helps.
x = (-b +/- √(b^2 - 4ac) ) / 2a
where a, b and c are the coefficients of the quadratic equation with the form ax^2 + bx + c=0
Therefore, the quadratic equation would be:
a = 3
b = -6
c = 8
x = (-(-6) +/- √((-6)^2 - 4(3)(8) ) / 2(3)
Hope this helps.
Answer:
The correct answer is:
[tex]x = \frac{6 +- \sqrt{(-6)^2-4x3x8} }{2(3)}[/tex]
Step-by-step explanation: